The Reality of Algerian Banking Sector Commitment to Social Responsibility Principles & its Contribution to Encouraging SMES to Adopt a Culture of Sustainable Social & Environmental Practices - Brahmia, Ammar; Mahri, Abdelmalek (Finance and Business Economies Review, 2022)
The study aims to show that the social responsibility of banks is an effective mechanism to support the sustainability of social and environmental practices of small and medium enterprises - a field study of banks operating in tebessa, To test the hypotheses of the study, a set of statistical methods, such as arithmetic mean, standard deviation and T test for a single sample